Verification of model predicted precipitation over India during the summer monsoon of 1997 (MAUSAM, 2003)
For the monsoon season of 1997 the precipitation observation from 1333 rain gauge stations are used to form spatial averages for 135 grid points of the NCMRWF forecast model covering the whole of India. These spatial averages are compared with the model forecasts of precipitation by computing the mean error, mean absolute error, root mean square error and correlation coefficient. The skill of forecast is also computed by discretizing the precipitation amounts in  to standard categories.                 The seasonal accumulated precipitation and its spatial distribution are well reproduced in the model predictions up to 4-days in advance. The mean error in prediction shows spread of precipitation across the Western Ghat hills as the barrier effect is under estimated in the model due to poor horizontal resolution. The correlation coefficient shows good in-phase relationship between the predicted and observed precipitation especially over areas of very large seasonal precipitation. Over a small area this coefficient has values higher than 0.6. The model has skill for categories of precipitation with class mark up to 1.0 inch and prediction lead-time up to 2 day.  In 1997 no low frequency south to north propagating mode is present in the observed box average precipitation.